Governança corporativa em cenário de mudanças: evidências empíricas das alterações dos atributos, papéis e responsabilidades do conselho de administração das empresas brasileiras - Henrique Cordeiro Martins (2005)
Discussions on the corporate governance have become particularly important for the integrating character that this instance of power in the companies assumes in the new international financial conjunction, strengthening the markets of capitals in the countries. In that sense, the board of directors is seen as the central instrument of governance, promoting the interaction between the shareholders and other stakeholders, the market corporate control and the corporate finance systems. The objective of this thesis is to analyze the corporategovernance characteristics and the impacts in the attributes, roles and responsibilities of the board of directors of the Brazilian companies, starting from the changes provoked by the globalization, privatization and the new global structure of businesses, as well as the adoption of shareholder value. Therefore, the research of quantitative and qualitative nature was accomplished in the 300 largest Brazilian companies listed in BOVESPA, from the board and management point of view. The quantitative part of this thesis is characterized as a survey,accomplished ex-post facto, in a inter-sectional line. And the work method used in the qualitative part it was the study of multiple cases, in 10 companies. The selected results point that the composition of the attributes of the board of the researched companies are morestrongly linked to the controling role, although the numbers reveal the importance given by the board to the strategic role. Nonetheless, a clear conscience that the work of the board creates value for the company is observed, but actually, this conscience is not translated into practice.